Forming limit prediction of advanced high-strength steels (AHSS) using an enhanced ductile damage model - Hao, Nguyen H. (Vietnam Journal of Mechanics, 2025)
This paper presents prediction of forming limits of Advanced High-Strength Steels (AHSS) DP980 by adopting an enhanced ductile damage model to consider sheet metal anisotropy. The micro-void growth-based original damage model is transformed from principal stress space (σ1, σ2, σ3) into the equivalent stress, Lode parameter, and stress triaxiality space (σe, Lp, η). The proposed ductile fracture prediction model is then implemented and integrated with a finite element (FE) software package to conduct the deep drawing numerical simulations. The Nakajima-type specimens are adopted to predict the limiting principal plastic strains ranging from uniaxial tensile through plane-strain to biaxial tensile loading states. The forming limit diagram (FLD) of DP980 steel is established in accordance with the ISO 12004-2-2008 standard.